The Animal Origin of Major Human Infectious Diseases: What Can Past Epidemics Teach Us About Preventing the Next Pandemic? - Guha Dharmarajan; Ruiyun Li; Emmanuel Chanda; Katharine R. Dean; Rodolfo Dirzo; Kjetill S. Jakobsen; Imroze Khan; Herwig Leirs; Zheng-Li Shi; Nathan D. Wolfe; Ruifu Yang; Nils Chr. Stenseth (Zoonoses)
Emerging infectious diseases are one of the greatest public health challenges. Approximately three-quarters of these diseases are of animal origin. These diseases include classical zoonoses maintained in humans only via transmission from other vertebrates (e.g., rabies) and those initiated by a successful one-off zoonotic event (host-switch) in conjunction with efficient human-to-human transmission (e.g., H1N1 influenza). Here, we provide a systematic review, in conjunction with a meta-analysis and spatial risk modeling, to identify the major characteristics of past epidemics of animal origin and predict areas with high future disease emergence risk. Countermeasures against future pandemics of animal origin must focus on several key mechanisms. First, the eco-epidemiological contexts favoring spillover events must be clearly establish. Second, pathogen surveillance must be scaled up, particularly in taxa and/or eco-geographic areas with high disease emergence risk. Third, successful spillover risk must be mitigated through proactive strategies to interrupt animal-to-human transmission chains. Fourth, to decrease epidemic potential and prevent epidemics from becoming pandemics, improved source identification and real-time spatial tracking of diseases are crucial. Finally, because pandemics do not respect international borders, enhancing international collaboration is critical to improving preparedness and response.